Banana fibers and rigid pvc composites: Effect of fiber treatment Compósitos de pvc rígido e fibras de bananeira: Efeito do tratamento da fibra - Kleinschmidt A.C. (2014)
© 2014, Universidade Federal do Rio de Janeiro. All rights reserved.The interest in natural fiber composites with thermoplastic polymers is growing every year. Natural fibers have advantages such as low density, low abrasion, low cost, are biodegradable and self-sustainable, since they are natural and renewable source. Among the thermoplastic resins viable for employment fiber banana stands out poly (vinyl chloride) - PVC for its versatility compared to its formulation, because there is the need to incorporate additives during processing, making adaptable to multiple applications. The objective of this work was to study the influence of type of banana fibers (FB) treatment in the properties of rigid poly (vinyl chloride) (PVC). Mechanical properties, thermal stability and water absorption of composite PVC/FB were evalueted for the effect of alkaline treatments, with maleic anhydride and acetylation of banana fibers. The composites were obtained in two-roll open mixer followed by injection of test samples. The results indicate that treatment with maleic anhydride and acetylation exhibit better impact resistance and lower water absorption than the alkaline treatment. The thermal properties did not change significantly with the addition of banana fibers treated and untreated.